Anmeldelser - Jacobsen, Niels Kingo; Jensen, Ruth Helkiær (Geografisk Tidsskrift, 1965)
Indholdsfortegnelse Litteraturanmeldelser: FYSISK GEOGRAFI M. M. F. A. Vening Meinesz: The Earth’s Crust und Mantle (K. Hansen) ........ 105 L. U. de Sitter: Structural Geology (K. Hansen) .......................... 106 R. Brinkmann: Lehrbuch der Allgemeinen Geologie (K. Hansen) ........ 122 Observer’s Handbook (Kr. M. Jensen) ..................................... 107 The Marine Observer’s Handbook (Kr. M. Jensen) ....................... 107 G. T. Trewartha: An Introduction to Climate (Kr. M. Jensen) ............ 106 J. Bucknell: Climatology: an introduction (Kr. M. Jensen) ............. 107 F. Baur: Grosswetterkunde und Langfristige Witterungsvorhersage (Kr. M. Jensen) ....................................................... 108 J. Kakas: Einfluss der Karpaten auf die Witterungserscheinungen (Kr. M. Jensen) ............... 108 H. H. Lamb: The English Climate (Kr. M. Jensen).......................... 107 J. Blüthgen: Allgemeine Klimageographie (Kr. M. Jensen) ............... 120 H. A. Gleason & A. Cronquist: The Natural Geography of Plants (Kr. M. Jensen) ....................................................... 108 H. Walter: Die Vegetation der Erde in öko-physiologischer Betrachtung (Kr. M. Jensen) ....................................................... 109 A. W. Kiichler: Potential Natural Vegetation of the Conterminous United States (N. Nielsen) .................................................... 109 G. Millot: Géologie des Argiles (K. Hansen) .............................. 105 D. G. Frey: Remains of animals in Quaternary lake and bog sediments and their interpretation (K. Hansen) ................................ 106 KULTUR- OG ERHVERVSGEOGRAFI H. Boesch: A Geography of World Economy (H. Kuhlman) ............. 116 W. Warntz: Geography now and then (N. Nielsen) ........................ 121 R. W. Steel & R. M. Prothero: Geographers and the Tropics: Liverpool Essays (Aa. Aagesen) ................................................ 118 Advances in Agronomy (H. Kuhlman) ..................................... 125 F. Bartz: Die grossen Fischereiräume der Welt, Bd. I. (N. Nielsen) ..... 117 F. Bartz: Die grossen Fischereiräume der Welt, Bd. II. (N. Nielsen) ...... 121 Colloque National de Géographie Appliquée (N. Nielsen) ................. 102 EUROPA OG SOVJETUNIONEN F. J. Monkhouse: A Regional Geography of Western Europe (V. Hansen) 112 J. M. Houston: The Western Mediterranean World (V. Hansen) .......... 112 R. Millward: Scandinavian Lands (N. Nielsen) ............................ 110 N. Rrantzeg: Riant Frender pä Fzeroyene (Aa. H. Kampp) ............... 110 E. Rehhen: Essor et Problemes de 1’Agriculture danoise (N. Nielsen) . ... 110 O. F. Geyer & M. P. Gwinner: Einführung in die Geologie von Raden- Württemberg (K. Hansen) ............................................ 122 W. Czajka: Der Schlesische Landrücken (N. Nielsen) ..................... 104 D. Rartels: Das Maures-Rergland (N. Nielsen) ............................ 105 R. H. Rest & J. T. Coppock: The Changing Use of Land in Britain (V. Hansen) ........................................................... 111 J. Rird: The Major Seaports of the United Kingdom (V. Hansen) ........ 111 J. P. Cole & F. C. German: A Geography of the USSR (V. Hansen) ........ 112 P. E. Lydolph: Geography of the U.S.S.R. (V. Hansen) ................... 113 R. E. H. Mellor: Geography of the U.S.S.R. (V. Hansen) ................. 113 FREMMEDE VERDENSDELE C. L. White, E. J. Foscue & T. L. McKnight: Regional Geography of Anglo- America (N. Nielsen) ................................................ 114 J. P. Powelson: Latin America (R. H. Jensen) ............................ 116 H. Wilhelmy & W. Rohmeder: Die La Plata-Länder. Argen.tinien-Paraguay- Uruguay (Aa. Aagesen) .............................................. 119 P. Camu, E. P. Weeks, Z. W. Sametz: Economic Geography of Canada (V. Hansen) ............................................................ 115 L. Dudley Stamp: Africa. A Study in Tropical Development. 2nd. ed. (Aa. Aagesen) ......................................................... 119 R. J. Harrison Church m. fl.: Africa and the Islands (Aa. Aagesen) ...... 123 W. Hcllmich: Khumbu Himal (N. Nielsen) ................................. 103 E. Kaempfer: Geschichte und Reschreibung von Japan I II (N. Nielsen) . . 114 S. Wadham, R. Kent Wilson & J. Wood: Land Utilization in Australia (R. H. Jensen) ....................................................... 121 POLAREGNENE W. Dege: Grönland ohne Eskimos (B. Fristrup) ........................ 124 Axel Heiberg Islands Research Reports (N. Nielsen) ...................... 103 M. Mellor: Antarctic Snow and Ice Studies (B. Fristrup) ................. 124 Antarctic Research. A Review’ of British Scientific Achievement in Antarctica (B. Fristrup) ......................................................... 123 Soviet Antarctic Expedition (B. Fristrup) ................................ 123 ATLASVJERKER OG KORT A. Ortelius: Theatrum Orbis Terrarum, 1570 (N. Nielsen) ................. 101 L. Jansz Waghenaer: De Spieghel der Zeevaerdt. 1584-85 (N. Nielsen) . .. . 101 T. Eastwood: Stanford’s Geological Atlas of Great Britain (K. Hansen) . . . . 122 J .T. Coppock: An Agricultural Atlas of England and Wales (V. Hansen) 102 Deutscher Planungs Atlas (N. Nielsen) ..................................... 100 NYE TIDSSKRIFTER M. M. Geophysik und Geologie (K. Hansen) ..................................... 105 B0GER INDGÅET TIL REDAKTIONEN ................ 127